Βλημενοσ Ην (Iliad 4.211): Lexical or Periphrastic?. Issue 1 (1st January 2017) - Bentein, Klaas; Janse, Mark
Abstract : In this article, we consider whether the form βλήμενος ἦν in Il . 4.211 should be considered lexical or periphrastic. Based on a discussion of the context, an analysis of the usage of the verb βάλλω elsewhere in the Iliad, and an application of some generally accepted criteria of periphrasticity, we conclude that both interpretations are in fact possible. We connect this to the diachronic development of periphrastic constructions, which, in an early stage of grammaticalization, are often ambiguous.